The Relationship between Marketing Mix and Customer Loyalty in the Fmcgs Stores in South Africa - Ruth Soda; Olabanji Oni; Solomon Omonona (Re-engineering Business Processes in the New Normal - The Business and Economic Development Post COVID-19 and the Restructuring of the Global Economy: Proceedings of 8th International Conference on Business and Management Dynamics, 2023)
The study seeks to analyse the effects of marketing mix on customer loyalty. While the specific objectives were to determine the relationship between price, promotion, place, product and customer loyalty. Quantitative research survey design was adopted for the study, both primary and secondary sources of data were utilised during the investigation. Data was collected via questionnaires and analysed utilizing ANOVA test and multiple regression. Hence, it was discovered that there exists a positive relationship between the marketing mix elements and customer loyalty. It also evident that business’ operations are centred on satisfying the needs of customers so that they remain loyal. Therefore, making the marketing mix a crucial tool for business’ success. The study recommends that the supermarkets in King Williams Town should stock superior and unique products, which satisfy the needs of customers and of course, intense promotion should be encouraged i.e. advertising, personal selling, packaging as well as their branding skills whilst making sure those products are well distributed in order to boost customer loyalty.